Free radical photopolymerization initiated by UV and LED: Towards UV stabilized, tack free coatings. Issue 24 (6th October 2014) - Karasu, Feyza; Croutxé‐Barghorn, Céline; Allonas, Xavier; Van Der Ven, Leendert G.J.
ABSTRACT UV stabilizers (UV absorbers and Hindered Amine Light Stabilizers‐HALS) are added to UV‐curable formulations to provide long‐term durability. The influence of HALS and the filtering effect of UV absorbers are investigated under UV and LED irradiation by using different photoinitiating systems in free radical photopolymerization. The contribution of irradiation conditions and initiating systems on the filtering effect is discussed by performing Real‐Time Fourier Transform Infrared Spectroscopy (RT‐FTIR) and Confocal Raman Microscopy. Additionally, to get quantitative information about the light absorbed by the photoinitiator, without and with the filtering issue arising from UV stabilizers, series of calculations are carried out by taking into account the amount of light absorbed by the compounds and the intensity of the incident light. Finally, formulations are optimized with respect to surface inhibition to obtain tack free coatings in air atmosphere in the presence of UV stabilizers under visible light. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 3597–3607